Effect of oxytetracycline hydrochloride coating added to Compudose implants in grazing steers - Lomas, Lyle W. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Adding an oxytetracycline coating to Compudose implants did not change their effectiveness. Implanting with Compudose significantly increased gain of grazing steers an average of 17% compared to non-implanted controls.
Keywords: Beef; Oxytetracycline hydrochloride; Implants; Steers